„Obszar zagospodarowany wyobraźnią” (1970) Ewy Partum wobec lokalnych infrastruktur sztuki - Karolina Majewska-Güde (Miejsce)
The text focuses on a historicisation and a new interpretation of Ewa Partum’s diploma intervention from 1970 as analysed in relation to the artist’s diploma thesis and the installation ”Zone of the Imagination”. To articulate the meaning of this piece of Partum’s artistic practice, the author proposes to frame it within the discourse on art infrastructures. The notion of institutional critique remains the hidden object of the study while being revised and rewritten, following the paradigm of horizontal art history and the concept of the parallax effect.